NOTA PRELIMINAR SOBRE UMA NOVA MOLESTIA DE VIRUS DO ALGODOEIRO: MOSAICO DAS NERVURAS - Costa, A. S.; Forster, R. (REVISTA DE AGRICULTURA, 2015)
NOTA PRELIMINAR SOBRE UMA NOVA MOLESTIA DE VIRUS DO ALGODOEIRO: MOSAICO DAS NERVURAS